A Universal Principle to Design Reversible Aqueous Batteries Based on Deposition–Dissolution Mechanism. Issue 32 (18th July 2019) - Liang, Guojin; Mo, Funian; Li, Hongfei; Tang, Zijie; Liu, Zhuoxin; Wang, Donghong; Yang, Qi; Ma, Longtao; Zhi, Chunyi
Abstract: Conventional charge storage mechanisms for electrode materials are common in widely exploited insertion/extraction processes, while some sporadic examples of chemical conversion mechanisms exist. It is perceived to be of huge potential, but it is quite challenging to develop new battery chemistry to promote battery performance. Here, an initiating and holistic deposition–dissolution battery mechanism for both cathodes and anodes is reported. A MnO2 –Cu battery based on this mechanism demonstrates outstanding energy density (27.7 mWh cm −2 ), power density (1232 mW cm −2 ), high reversibility, and unusual Coulombic efficiency. It can be charged to 0.8 mAh cm −2 within 42 s and possessees a stable rate cyclability within vastly varied discharging current density (4–64 mA cm −2 ). Moreover, the deposition–dissolution mechanism can be universally adopted and derived such that the corresponding MnO2 –Zn and MnO2 –Bi batteries are successfully constructed. The material selection principle, deposition–dissolution behaviors of cathode/anode materials, and battery performance are systematically elaborated. Since the electrodeposition chemistry is capable of involving a large family of materials, for example, metal oxides as cathode materials, or metals as anode materials, the research could be a model system to open a door to explore new aqueous battery materials and chemistry. Abstract : Deposition–dissolution mechanism is developed to design reversible aqueous batteries, which are verified as a universal principle by selecting MnO2 as cathode materials and three different metals (Cu, Zn, and Bi) as anode materials. The battery design process is elaborated and as‐fabricated batteries deliver impressive performance, such as stable rate performance, high energy density, and long‐term cyclic stability.